The Rich Get Richer and the Poor Get Robbed: Inequality in U.S. Criminal Victimization, 1974–2000 - Thacher, David (Journal of quantitative criminology, 2004)
This paper investigates inequality in criminal victimization in the United States over the past quarter century. By analyzing data from the National Crime Victimization Survey, it shows that the crime drop since the early 1970s has benefited upper-income households much more than the poor, so that criminal victimization has become more concentrated among the poor (particularly in the area of nonstranger violence). The paper then decomposes this trend statistically in order to investigate factors that may explain it. That analysis finds that demographic changes in each quintile explain a significant share of the growing concentration of criminal victimization among the poor.